Spatial distribution and determinants of fertility preferences among female adolescents and young adults in Ethiopia - Melaku Birhanu Alemu; Zohra S. Lassi; Samrawit Birhanu Alemu; Ammar Bishaw Ebrahim; Daniel Gashaneh Belay; Gizachew A. Tessema (PLoS ONE, 2026)
Introduction Understanding adolescents and young adults’ (AYAs) fertility preferences is crucial for guiding youth-focused family planning and predicting future fertility. However, fertility preference determinants and spatial patterns among Ethiopian AYAs remain underexplored. This study examines the spatial distribution and determinants of fertility preferences among female AYAs in Ethiopia. Methods We analysed the nationally representative 2016 Ethiopian Demographic and Health Survey, the most recent standard survey containing fertility preference data. Fertility preference was defined as the ideal number of children respondents would like to have over their lifetime. Negative binomial regression was used to assess associations between fertility preference and sociodemographic factors, while Bayesian model-based geostatistics was employed to predict the spatial distribution of fertility preferences. Sampling weights were applied to account for the complex survey design. Results A total of 5762 females aged 15−24 years were included in the analysis. The mean preferred ideal number of children among AYAs was 3.68 (95% confidence interval: 3.63, 3.74). Primary education (IRR: 0.91), higher education (Incidence Rate Ratio (IRR): 0.92), being unmarried (IRR: 0.86), and residing in large central areas (IRR: 0.90) were associated with a preference for fewer children. Being Muslim (IRR: 1.13), protestant (IRR: 1.17) and rural resident (IRR: 1.06) were associated with preference for more children. There was a significant spatial variation in fertility preferences. Respondents who resided in Somalia, Afar, and the western part of Gambella were found to have higher fertility preferences. The spatial regression analysis identified travel to a city (0.14, 95% Credible Interval (CI): 0.10, 0.18), urbanisation (−0.08 CI: −0.11, −0.05), income (−0.05; CI: −0.06, −0.04), and literacy (−0.06, CI −0.02, −0.01) were significant raster level predictors. Conclusion Fertility preferences among female AYAs varied by sociodemographic characteristics, with Somali, Afar, and western Gambella regions showing higher preferences. These findings emphasise the need for context-specific policies and programs that address regional, cultural, and educational disparities. Targeted interventions in rural and underserved regions, coupled with initiatives to enhance education, empower young women, are essential to support informed and autonomous reproductive decision-making among AYAs.